Abdominal wall defect repair material as well as preparation method and application thereof
By dropping chitosan viscosity solution on the matrix layer of the abdominal wall defect repair material and loading puerarin, the problems of insufficient postoperative complications and vascularization performance of existing materials are solved, and efficient repair and reduction of abdominal wall defects are achieved. Postoperative risk.
Patent Information
- Application Number
- CN202411729185.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing abdominal wall defect repair materials are prone to complications such as chronic inflammation, patch infection, chronic pain and other complications after surgery, and lack early vascularization and self-adhesion properties, which extends the operation time and increases the risk of recurrence.
An abdominal wall defect repair material was designed to form a multifunctional repair material with self-adhesion properties by dropping chitosan sticky solution onto the matrix layer, and loading puerarin into the material to promote angiogenesis and tissue repair.
This material can sustainably release puerarin, synchronously achieve performances such as promoting angiogenesis and self-adhesion, significantly improve the repair effect of abdominal wall defects, reduce the risk of postoperative complications, and reduce the surgical time.
Smart Images

Figure CN119455098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices and preparation thereof, in particular to an abdominal wall defect repair material and a preparation method and application thereof. Background Art
[0002] Abdominal wall defects are common surgical diseases, mostly occurring in incisional hernias after surgery, accounting for more than 65% of abdominal wall defects. In addition, abdominal or abdominal wall trauma, infection, and abdominal wall tumor resection can all cause severe and complex abdominal wall defects. The abdominal wall not only protects the organs in the abdominal cavity, but also plays a very important role in maintaining body balance, spinal stability, and assisting breathing, childbirth, defecation and other physiological functions. Complex abdominal wall defects can cause abdominal wall dysfunction, leading to kyphosis, decreased abdominal cavity pressure, venous return and other disorders. In addition, abdominal wall hernias can cause intestinal obstruction, even intestinal incarceration and strangulation, causing necrosis, perforation, peritonitis, and even death of the patient. Therefore, when abdominal wall defects occur, they should be treated promptly and effectively.
[0003] Surgery is the gold standard for the treatment of abdominal wall defects. Tension-free patch repair is the main surgical procedure, which can achieve good results. Composite patches made of polypropylene, polyester and their derivatives have good mechanical properties, but they are prone to induce complications such as chronic inflammation, patch infection, and chronic pain. Biological patches have good biocompatibility, but their application is still limited by their complex decellularization process, high cost and high recurrence rate. At the same time, the tissue remodeling ability of the above patches is poor, especially non-absorbable synthetic patches. In addition, these patches do not have adhesion properties and require mechanical fixation, which prolongs the surgical operation time and exposure risk.
[0004] Early vascularization of the scaffold is a prerequisite for repairing abdominal wall defects. Hydrogel is a polymer with a three-dimensional network structure. Due to its porous structure similar to the natural extracellular matrix, good biocompatibility, high hydrophilicity and adjustable mechanical properties, it has attracted increasing attention in the fields of tissue regeneration, drug delivery and wound dressing. However, traditional hydrogels have poor tissue remodeling ability, which limits the repair effect. Delivering functional drugs through hydrogels is an effective solution to improve the angiogenesis ability of scaffolds. Puerarin (Pue) is a natural Chinese herbal medicine extracted from Pueraria lobata. It accelerates tissue repair by reducing inflammation, regulating macrophage M2 polarization, and promoting angiogenesis and collagen synthesis. It has been clinically used to treat pelvic organ prolapse, osteoporosis, osteoarthritis and other inflammatory-related diseases. In view of this, designing a multifunctional patch loaded with puerarin to efficiently promote the repair of abdominal wall defects is an effective solution to solve the complications of traditional patches after surgery.
[0005] In addition to the poor early vascularization ability of the patch, current hernia repair materials also require mechanical fixation, which prolongs the operation time and increases the incidence of complications. Mechanical fixation often leads to stress concentration at the puncture point, causing pain, adhesion and scar formation. These scar tissues tend to wrap the entire patch, causing the patch to shrink. Therefore, surgical glue has been widely used to replace these mechanical fixation techniques to reduce postoperative complications. Commonly used glues for fixing hernia patches include fibrin glue or cyanoacrylate glue. However, the adhesion strength and biocompatibility of the glue make it difficult to achieve satisfactory results, increasing the risk of postoperative complications.
[0006] Patent CN110038163A uses an enzymatic cross-linking method to make a patch from gelatin and porcine decellularized dermal matrix powder. The preparation process is complex and has pro-vascularization properties, but lacks adhesion properties, and mechanical fixation is still required during surgery; Patent CN114984323B composites the decellularized dermis layer with an electrospinning film layer, and then immerses it in placental tissue slurry to obtain an abdominal wall defect repair material with good biocompatibility, antibacterial and anti-inflammatory activities. Its preparation process requires a complex decellularization process and lacks pro-vascularization and adhesion properties; Patent CN115591020A invents an acellular dermal matrix patch that retains a natural collagen structure, but has problems such as a complex decellularization process, high cost, and a high recurrence rate, and the resulting patch lacks pro-vascularization and adhesion properties.
[0007] Therefore, it is of great clinical significance to design a patch with early vascularization and self-adhesion properties to efficiently repair abdominal wall defects. Summary of the invention
[0008] The purpose of the present invention is to provide an abdominal wall defect repair material and a preparation method and application thereof, so as to solve the problems raised in the prior art.
[0009] To achieve the above object, the present invention provides the following technical solution: an abdominal wall defect repair material, comprising a matrix layer and a chitosan adhesion layer,
[0010] Furthermore, a chitosan viscous solution is dripped onto the surface of the matrix layer.
[0011] Furthermore, the abdominal wall defect repair material is loaded with puerarin.
[0012] A method for preparing an abdominal wall defect repair material comprises the following steps:
[0013] S1: acrylamide, sodium alginate, calcium sulfate, ultra-low viscosity sodium alginate, puerarin and deionized water are mixed, stirred to dissolve, and a mixed solution is obtained. An initiator, a cross-linking agent and a catalyst are added to the mixed solution, stirred for 20-30 minutes, and sealed at low temperature for reaction to obtain a matrix layer;
[0014] S2: Add chitosan viscous solution on the surface of the matrix layer to obtain the abdominal wall defect repair material.
[0015] Furthermore, the ratio of the matrix layer to the chitosan viscous solution is 20-25 μL / mm 2 .
[0016] Furthermore, the process conditions for stirring and dissolving are: temperature 20-25° C., time 8-12 h.
[0017] Furthermore, the process conditions of the low-temperature sealing reaction are: temperature 0-4°C, time 20-24h.
[0018] Furthermore, the mass ratio of acrylamide, sodium alginate, calcium sulfate, ultra-low viscosity sodium alginate, puerarin, and deionized water is (11-12): (0.75-1): (2.5-2.7): (0.75-1): (0.22-0.25): 100.
[0019] Further, the ratio of the mixed solution, initiator, and cross-linking agent is 100 mL: (0.12-0.14) mg: (0.064-0.066) mg;
[0020] The volume ratio of the mixed solution to the catalyst is 100:(0.08-0.2).
[0021] Further, acrylamide: CAS number is 79-06-1, derived from MacLean's reagent;
[0022] Sodium alginate: CAS number is 9005-38-3, viscosity is 180-220mPa·s, from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.
[0023] Ultra-low viscosity sodium alginate: viscosity is 3-5mPa·s, sourced from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.
[0024] Calcium sulfate: CAS number is 7778-18-9, purity is 99%, from Shanghai Jieshikai Biotechnology Co., Ltd.
[0025] Puerarin: CAS number is 3681-99-0, sourced from Chengdu Mansite Biotechnology Co., Ltd.
[0026] Further, the initiator is ammonium persulfate, CAS No. 7727-54-0, derived from Merck reagent;
[0027] The cross-linking agent is N,N-methylenebisacrylamide, CAS No. 110-26-9, which is derived from Merck reagents;
[0028] The catalyst is tetramethylethylenediamine, CAS No. 110-18-9, which is from Thermo Fisher Scientific Inc.
[0029] In the above technical scheme, free radical polymerization occurs between acrylamide chains, sodium alginate and calcium ions are cross-linked to form a double network hydrogel, and a chitosan viscous solution is dripped on the surface to form a multifunctional repair material with excellent mechanical properties, strong adhesion and sustained release of puerarin. Acrylamide and sodium alginate have good mechanical properties and can resist the maximum intra-abdominal pressure and reduce the risk of hernia recurrence. The chitosan viscous layer has strong adhesion properties, and no mechanical fixation is required during the operation, which shortens the operation time, avoids stress concentration at the puncture site caused by mechanical fixation, and reduces patch shrinkage caused by scar formation. The loaded puerarin has the functions of anti-inflammatory, promoting macrophage M2 polarization, anti-oxidation, promoting angiogenesis and collagen deposition, etc., which realizes efficient reconstruction of abdominal wall defects. Acrylamide, sodium alginate and chitosan are all excellent bio-friendly matrices, and the prepared abdominal wall defect repair material has good biocompatibility, and has the properties of anti-oxidation, anti-inflammatory, immunomodulatory, promoting angiogenesis, collagen deposition, etc., thereby accelerating tissue repair.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. Puerarin is loaded on acrylamide and sodium alginate to form a matrix layer, and a chitosan adhesive layer is polymerized on its surface. The resulting abdominal wall defect material can slowly release puerarin, simultaneously achieve the properties of promoting angiogenesis and self-adhesion, and can efficiently repair abdominal wall defects.
[0032] 2. The abdominal wall defect repair material prepared by the present invention has a porous structure, good biocompatibility, high porosity, and can provide sufficient three-dimensional space for cell adhesion and growth.
[0033] 3. The abdominal wall defect repair material prepared by the present invention has excellent mechanical properties, can withstand the maximum intra-abdominal pressure, reduce the risk of recurrence, and protect wound healing.
[0034] 4. The abdominal wall defect repair material prepared by the present invention has strong self-adhesive properties, and does not require suturing during surgery, which reduces the operation time and avoids scar formation caused by mechanical fixation, which causes patch shrinkage.
[0035] 5. The abdominal wall defect repair material prepared by the present invention has strong antibacterial properties, which is of great significance for preventing postoperative infection.
[0036] 6. The abdominal wall defect repair material prepared by the present invention can be synthesized by a one-step method, which meets the clinical requirements for an ideal abdominal wall repair material. The selected components are also commonly used materials with excellent biocompatibility, which makes the patch low in cost and easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic diagram of the surface structure of the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention.
[0038] Figure 2 This is a schematic diagram of the surface structure of the abdominal wall defect repair material obtained in Example 3 of the present invention.
[0039] Figure 3 This is a schematic diagram of the cross-sectional structure of the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention.
[0040] Figure 4 This is a schematic diagram of the cross-sectional structure of the abdominal wall defect repair material obtained in Example 3 of the present invention.
[0041] Figure 5 This is a comparison chart of infrared spectra of the abdominal wall defect repair materials obtained in Example 3 of the present invention and Comparative Example 1.
[0042] In the figure, a represents the abdominal wall defect repair material obtained in Comparative Example 1, and b represents the abdominal wall defect repair material obtained in Example 3; the abscissa represents the wave number, and the ordinate represents the transmittance.
[0043] Figure 6 This is a schematic diagram showing the effect of storage days on the release of puerarin from the abdominal wall defect repair material obtained in Example 3 of the present invention.
[0044] In the figure, the horizontal axis represents time, and the vertical axis represents the release percentage.
[0045] Figure 7 This is a comparison chart of the mass expansion ratios of the abdominal wall defect repair materials obtained in Example 3 of the present invention and Comparative Example 1.
[0046] In the figure, the horizontal axis represents time, and the vertical axis represents mass expansion ratio.
[0047] Figure 8-10 These are, respectively, the initial state, the state when pressure is applied, and the state after recovery of the abdominal wall defect repair material obtained in Comparative Example 1.
[0048] Figure 11-13 These are, respectively, the initial state, the state when pressure is applied, and the state after recovery of the abdominal wall defect repair material obtained in Example 3.
[0049] Fig.14 This is a comparison chart of the mechanical property test results of the abdominal wall defect repair materials obtained in Example 3 of the present invention and Comparative Example 1.
[0050] In the figure, the horizontal axis represents the degree of injury, and the vertical axis represents the pressure; a represents the abdominal wall defect repair material obtained in Example 3; b represents the abdominal wall defect repair material obtained in Comparative Example 1, and c represents polyacrylamide.
[0051] Figure 15-16 This is a schematic diagram of the abdominal wall defect repair material obtained in Example 3 of the present invention adhered to glass.
[0052] Figure 17-18 This is a schematic diagram of the abdominal wall defect repair material obtained in Example 3 of the present invention adhered to pork.
[0053] Figure 19-20 This is a schematic diagram of the abdominal wall defect repair material obtained in Example 3 of the present invention adhering to rubber.
[0054] Fig.21 This is a schematic diagram of the abdominal wall defect repair material obtained in Example 3 of the present invention adhered between two pieces of pork.
[0055] In the figure, the hanging weight is 200g.
[0056] Fig. 22 This is a bar graph showing the bacterial inhibition rate of the chitosan adhesion layer in Example 3 of the present invention.
[0057] In the figure, E.coli is Escherichia coli, S.aureus is Staphylococcus aureus, and the vertical axis is the bacterial inhibition rate.
[0058] Figure 23-24 Schematic diagrams of the number of Escherichia coli before and after contacting with the chitosan adhesion layer in Example 3 of the present invention.
[0059] Figure 25-26 Schematic diagrams of the number of Staphylococcus aureus before and after contacting with the chitosan adhesion layer in Example 3 of the present invention.
[0060] Fig. 27 This is a comparison chart of the DPPH scavenging ability of the abdominal wall defect repair materials obtained in Example 3 and Comparative Example 1.
[0061] In the figure, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3; the ordinate is the DPPH scavenging ability.
[0062] Figure 28-30 They are comparison diagrams of DPPH scavenging ability of the blank control group and the abdominal wall defect repair materials obtained in Example 3 of the present invention and Comparative Example 1.
[0063] In the figure, control is a blank control group, PAM-SA is the abdominal wall defect repair material obtained in comparative example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in example 3.
[0064] Figure 31-33The cell shape diagrams of the blank control group and the abdominal wall defect repair materials obtained in comparative example 1 and example 3 of the present invention co-cultured with macrophages are shown respectively.
[0065] In the figure, control is a blank control group, PAM-SA is the abdominal wall defect repair material obtained in comparative example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in example 3.
[0066] Figure 34-36 Schematic diagram of the expression capacity of M1 macrophage marker genes.
[0067] In the figure, control is a blank control group, PAM-SA is the abdominal wall defect repair material obtained in comparative example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in example 3.
[0068] Figure 37-39 Schematic diagram of the expression capacity of M2 macrophage marker genes.
[0069] In the figure, control is a blank control group, PAM-SA is the abdominal wall defect repair material obtained in comparative example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in example 3.
[0070] Fig.40 It is a comparison chart of the effects of the blank control group and the abdominal wall defect repair materials obtained in comparative example 1 and example 3 of the present invention on the migration of HUVEC (vascular endothelial cells).
[0071] In the figure, the ordinate represents the number of migrated cells, control is the blank control group, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3.
[0072] Figure 41-42 This is a comparison chart of the number of blood vessels and nodes of the abdominal wall defect repair materials obtained in the blank control group and comparative example 1 and example 3 of the present invention.
[0073] Fig.41 In the figure, the vertical axis represents the number of nodes. Fig.42 In the figure, the ordinate represents the number of small tubes, control is the blank control group, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3.
[0074] Figure 43-45 Schematic diagrams of the healing effects of PP (polypropylene) patch, PAM-SA and Pue@PAM-SA, respectively.
[0075] Fig.46This is a comparison chart of the collagen expression capabilities of PP (polypropylene) patch, PAM-SA and Pue@PAM-SA.
[0076] In the figure, the ordinate represents the collagen expression ability, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3.
[0077] Fig.47 A comparison of the relative coverage of macrophages (CD68) of PP (polypropylene) patch, PAM-SA and Pue@PAM-SA.
[0078] In the figure, the ordinate is the relative coverage, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3.
[0079] Fig.48 Comparison of the number of blood vessels generated for PP (polypropylene) patch, PAM-SA, and Pue@PAM-SA.
[0080] In the figure, the vertical axis represents the number of blood vessels, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3. DETAILED DESCRIPTION
[0081] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0082] The following specific implementation method is a laboratory test and can be scaled up in equal proportions;
[0083] In the following specific implementations,
[0084] Acrylamide: CAS number is 79-06-1, derived from McLean's reagent;
[0085] Sodium alginate: CAS number is 9005-38-3, from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.
[0086] Ultra-low viscosity sodium alginate: viscosity is 3-5mPa·s, sourced from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.
[0087] Calcium sulfate: CAS number is 7778-18-9, purity is 99%, from Shanghai Jieshikai Biotechnology Co., Ltd.
[0088] Puerarin: CAS number is 3681-99-0, from Chengdu Mansite Biotechnology Co., Ltd.
[0089] Ammonium persulfate, CAS number 7727-54-0, from Merck Reagents;
[0090] N,N-methylenebisacrylamide, CAS number 110-26-9, from Merck reagents;
[0091] Tetramethylethylenediamine, CAS No. 110-18-9, is from Thermo Fisher Scientific Inc.
[0092] Embodiment 1: A method for preparing an abdominal wall defect repair material, comprising the following steps:
[0093] S1: 2.2 g acrylamide, 0.15 g sodium alginate, 0.50 g calcium sulfate, 0.15 g ultra-low viscosity sodium alginate, 45 mg puerarin and 20 ml deionized water were mixed, stirred at 20°C for 8 h to fully dissolve them to obtain a mixed solution, 24 mg ammonium persulfate, 12.8 mg N,N-methylenebisacrylamide and 16 μL tetramethylethylenediamine were added to the mixed solution, stirred for 20 min, and sealed at 0°C for 20 h to react to obtain a matrix layer; S2: chitosan viscous solution was dripped on the surface of the matrix layer to obtain an abdominal wall defect repair material; the ratio of the matrix layer to the chitosan viscous solution was 20 μL / mm 2 .
[0094] Embodiment 2: A method for preparing an abdominal wall defect repair material, comprising the following steps:
[0095] S1: 2.3 g acrylamide, 0.17 g sodium alginate, 0.52 g calcium sulfate, 0.17 g ultra-low viscosity sodium alginate, 47 mg puerarin and 20 ml deionized water were mixed, stirred at 23°C for 10 h to fully dissolve, and a mixed solution was obtained. 26 mg ammonium persulfate, 13.0 mg N,N-methylenebisacrylamide and 25 μL tetramethylethylenediamine were added to the mixed solution, stirred for 26 min, and sealed at 2°C for 22 h to react to obtain a matrix layer; S2: chitosan viscous solution was dripped on the surface of the matrix layer to obtain an abdominal wall defect repair material; the ratio of the matrix layer to the chitosan viscous solution was 22 μL / mm 2 .
[0096] Embodiment 3: A method for preparing an abdominal wall defect repair material, comprising the following steps:
[0097] S1: 2.4 g acrylamide, 0.2 g sodium alginate, 0.54 g calcium sulfate, 0.2 g ultra-low viscosity sodium alginate, 50 mg puerarin and 20 ml deionized water were mixed, stirred at 25°C for 12 h to fully dissolve them to obtain a mixed solution, 28 mg ammonium persulfate, 13.2 mg N,N-methylenebisacrylamide and 40 μL tetramethylethylenediamine were added to the mixed solution, stirred for 30 min, and sealed at 4°C for 24 h to react to obtain a matrix layer; S2: chitosan viscous solution was dripped on the surface of the matrix layer to obtain an abdominal wall defect repair material; the ratio of the matrix layer to the chitosan viscous solution was 25 μL / mm 2 .
[0098] Comparative Example 1: Compared with Example 3, puerarin was not added when preparing the abdominal wall defect material, and other process conditions remained unchanged.
[0099] Experiment: Take the repair materials obtained in Example 3 and Comparative Example 1, test their properties respectively and record the test results; the repair material in Comparative Example 1 is PAM-SA, and the repair material in Example 3 is Pue@PAM-SA;
[0100] Pore size and structure test: Observe the surface and internal morphology of the repair material by scanning electron microscopy;
[0101] Depend on Figure 1-4 The test results show that both PAM-SA and Pue@PAM-SA have 3D porous structures with a pore size of about 40 μm, indicating that the addition of puerarin has no significant effect on the pore structure of the repair material. The repair material has a significant three-dimensional porous morphology, which is more conducive to the migration and growth of fibroblasts and helps repair abdominal wall defects.
[0102] Figure 5 The horizontal axis represents the wave number, and the vertical axis represents the transmittance; a represents PAM-SA, and b represents Pue@PAM-SA; Figure 5 It can be seen that compared with PAM-SA, Pue@PAM-SA has a -1 There is a new peak at , which is consistent with the peak of puerarin. Figure 6 The horizontal axis represents time, and the vertical axis represents the release percentage. Figure 6 It can be seen that puerarin in Pue@PAM-SA can be placed in PBS buffer for >14 days;
[0103] From the above test results, it can be seen that puerarin has been successfully loaded into the repair material and can achieve a sustained release effect, which will be more conducive to tissue repair.
[0104] Swelling ratio test: Take the repair materials prepared in Examples 1-3 and Comparative Example 1 to make samples and place them in a centrifuge tube. Record the original mass W0, then add PBS buffer to soak. Remove the soaking solution at different time points, dry it with filter paper and weigh it, which is recorded as W0. t , the expansion rate calculation formula is as follows:
[0105] Expansion rate = (W t -W0) / W0×100%;
[0106] Depend on Figure 7 It can be seen that the addition of puerarin will not have a significant effect on the mass expansion ratio of the repair material, and both Pue@PAM-SA and PAM-SA have good water stability.
[0107] Mechanical and adhesion performance test: Use a universal mechanical testing machine to test the mechanical strength and adhesion performance of the repair material;
[0108] Fig.14 The horizontal axis represents the degree of damage, and the vertical axis represents the pressure; a is Pue@PAM-SA, b is PAM-SA, and c is polyacrylamide; Fig.14 It can be seen that there is no significant difference in the tensile strength of PAM-SA and Pue@PAM-SA, which are 0.09MPa and 0.11MPa respectively, which are significantly higher than the maximum intra-abdominal pressure of 20kPa. Figure 1 5-20 shows that Pue@PAM-SA can not only adhere to pork, but also to glass and rubber. Fig.21 It can be seen that Pue@PAM-SA is tightly adhered between two pieces of pork and can withstand a load of 200 g;
[0109] Viscosity test: The repair materials obtained in Examples 1-3 and Comparative Example 1 were tested for viscosity using a viscometer SNB-1;
[0110] Burst pressure test: The repair materials obtained in Examples 1-3 and Comparative Example 1 were made into The sample is fixed on the bursting pressure test instrument, and deionized water is injected into the sample until the sample bursts and water seeps. The pressure at this time is recorded, which is the bursting pressure.
[0111] Average adhesion strength / kPa Burst pressure / mmHg Example 1 51 359 Example 2 53 368 Example 3 54 373 Comparative Example 1 52 370
[0112] Table 1 Viscosity test and burst pressure test results
[0113] As can be seen from the above table, the bursting pressure of Pue@PAM-SA is 373 mmHg, which is significantly higher than normal intra-abdominal pressure (5 mmHg), grade IV abdominal compartment syndrome (25 mmHg), and even higher than the maximum intra-abdominal pressure (150 mmHg); it can be seen that Pue@PAM-SA prepared by the present invention has stronger pressure resistance.
[0114] Antibacterial performance test: The adhesion layer with a diameter of 1 cm was co-cultured with Staphylococcus aureus and Escherichia coli for 24 hours, and the antibacterial rate was determined by colony counting;
[0115] Fig. 22 E.coli is Escherichia coli, S.aureus is Staphylococcus aureus, and the vertical axis is the bacterial inhibition rate; Fig. 22 It can be seen that after contacting with the adhesion layer, the number of colonies of Staphylococcus aureus and Escherichia coli growing on the agar plate decreased by 86.612±6.104% and 91.853±0.963%, respectively.
[0116] Antioxidant performance test: Pue@PAM-SA and PAM-SA were made into samples with a size of 0.5 cm × 0.5 cm, immersed in 1.5 mL DPPH solution for 24 h, and the supernatant was taken to measure the absorbance at a wavelength of 517 nm;
[0117] DPPH scavenging ability (%) = [(Ac-Am) / Ac] × 100%
[0118] In the formula, Ac refers to the absorbance of the DPPH solution without any treatment, and Am refers to the absorbance of the DPPH solution after being treated with the patch;
[0119] Depend on Fig. 27 It can be seen that the scavenging capacity of PAM-SA for DPPH is 12%, and the scavenging capacity of Pue@PAM-SA for DPPH is 75%;
[0120] Immunomodulatory performance test: PAM-SA and Pue@PAM-SA were co-cultured with RAW264.7 macrophages for 48 hours;
[0121] Figure 31-33 The cell morphologies of the blank control group, PAM-SA group, and Pue@PAM-SA group are shown respectively. The macrophages in the blank control group and PAM-SA group showed round and clustered morphologies, while the Pue@PAM-SA group showed elongated cell morphologies with obvious pseudopodia-like structures.
[0122] Figure 34-36 is the expression of M1 macrophage marker genes; Figure 34-36 It can be seen that the expression of M1 macrophage marker genes (CD80, CD86 and iNOS) in Pue@PAM-SA was significantly reduced, and the expression of M2 macrophage marker genes (CD163, CD206 and Arg-1) in Pue@PAM-SA was significantly increased. Figure 37-39is the expression of M2 macrophage marker genes; in the figure, control is the blank control group, PAM-SA is the abdominal wall defect repair material obtained in Comparative Example 1 of the present invention, and Pue@PAM-SA is the abdominal wall defect repair material obtained in Example 3; from the above results, it can be seen that Pue@PAM-SA can significantly promote the polarization of macrophages to M2 and reshape the immune microenvironment.
[0123] Angiogenesis promotion performance test: Prepare two sets of 96-well plates, add 50 μL of Pue@PAM-SA and PAM-SA diluted 1:1 with DEME (diethylene glycol methyl ethyl ether), place them in a 37°C incubator for 1 hour, co-culture Pue@PAM-SA and PAM-SA with HUVEC cells for 24 hours, and harvest 2.5×10 4 The cells were transferred to a 96-well plate and cultured at 37°C for 4 h. The angiogenesis was observed under a microscope, and the number of vascular branches and nodes was quantified using Image J software.
[0124] Depend on Fig.40 It can be seen that HUVEC (vascular endothelial cells) migrated the most in Pue@PAM-SA, Fig.41 , 42 It can be seen that Pue@PAM-SA has the largest number of blood vessels and nodes. These results indicate that Pue@PAM-SA can significantly promote the acceleration of new blood vessel formation and is beneficial to tissue repair.
[0125] Test of the repair effect of abdominal wall defects in rats: After anesthetizing SD rats with 3% sodium pentobarbital (1.5 mL kg-1) by intraperitoneal injection anesthesia, the hair in the abdominal area (from the xiphoid costal margin to the groin) was removed and disinfected with alcohol. A full-thickness defect with a diameter of 10 mm was constructed on the lateral abdominal wall; the PP (polypropylene) patch was sutured to the abdominal wall, and PAM-SA and Pue@PAM-SA were directly adhered to the abdominal wall without suturing. The patch was removed 14 days after the operation;
[0126] Depend on Figure 43-45 It can be seen that the healing effect of Pue@PAM-SA is better than that of PP (polypropylene) patch and PAM-SA.
[0127] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an abdominal wall defect repair material, characterized in that: The following steps are involved: S1: acrylamide, sodium alginate, calcium sulfate, ultra-low viscosity sodium alginate, puerarin and deionized water are mixed, stirred to dissolve, and a mixed solution is obtained. An initiator, a cross-linking agent and a catalyst are added to the mixed solution, stirred for 20-30 minutes, and sealed at low temperature for reaction to obtain a matrix layer; S2: Add chitosan viscous solution on the surface of the matrix layer to obtain the abdominal wall defect repair material.
2. The method for preparing an abdominal wall defect repair material according to claim 1, characterized in that: The mass ratio of acrylamide, sodium alginate, calcium sulfate, ultra-low viscosity sodium alginate, puerarin and deionized water is (11-12): (0.75-1): (2.5-2.7): (0.75-1): (0.22-0.25):
100.
3. The method for preparing an abdominal wall defect repair material according to claim 2, characterized in that: The ratio of the mixed solution, initiator and cross-linking agent is 100mL: (0.12-0.14)mg: (0.064-0.066)mg.
4. The method for preparing an abdominal wall defect repair material according to claim 2, characterized in that: The volume ratio of the mixed solution to the catalyst is 100:(0.08-0.2).
5. The method for preparing an abdominal wall defect repair material according to claim 1, characterized in that: The ratio of matrix layer and chitosan viscous solution is 20-25 μL / mm 2 .
6. The method for preparing an abdominal wall defect repair material according to claim 1, characterized in that: The process conditions for stirring and dissolving are: temperature 20-25°C, time 8-12h.
7. The method for preparing an abdominal wall defect repair material according to claim 1, characterized in that: The process conditions of low-temperature sealing reaction are: temperature 0-4°C, time 20-24h.
8. An abdominal wall defect repair material, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 6.
9. The use of an abdominal wall defect repair material according to claim 8, characterized in that: The abdominal wall defect repair material is applied to the abdominal wall defect after surgery.
Citation Information
Patent Citations
Preparation method of hydrogel composite biological patch for repairing abdominal-wall defects
CN110038163A
Absorbable chitin-based composite patch and application thereof
CN107029285A
Hydrogel patch capable of being used for repairing spinal dura mater defect, and preparation method and application of hydrogel patch
CN113491794A